2014
DOI: 10.1007/s00382-014-2330-2
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical structure of intense Mediterranean cyclones

Abstract: International audienceThis paper presents and analyzes the three-dimensional dynamical structure of intense Mediterranean cyclones. The analysis is based on a composite approach of the 200 most intense cyclones during the period 1989-2008 that have been identified and tracked using the output of a coupled ocean-atmosphere regional simulation with 20 km horizontal grid spacing and 3-hourly output. It is shown that the most intense Mediterranean cyclones have a common baroclinic life cycle with a potential vorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
138
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(158 citation statements)
references
References 68 publications
19
138
0
1
Order By: Relevance
“…Figure 3c shows the seasonal cycle of the 500 most intense cyclones in ERAI. All methods show a lower frequency of intense cyclones in summer and a higher one in spring and winter, in agreement with previous studies of intense Mediterranean cyclones (e.g., Campins et al 2011;Cavicchia et al 2014;Flaounas et al 2015b). …”
Section: Cosmo-clm/nemo-med12supporting
confidence: 80%
See 1 more Smart Citation
“…Figure 3c shows the seasonal cycle of the 500 most intense cyclones in ERAI. All methods show a lower frequency of intense cyclones in summer and a higher one in spring and winter, in agreement with previous studies of intense Mediterranean cyclones (e.g., Campins et al 2011;Cavicchia et al 2014;Flaounas et al 2015b). …”
Section: Cosmo-clm/nemo-med12supporting
confidence: 80%
“…These cyclones have a strong impact on the Mediterranean climate, its variability and extremes (e.g., Trigo et al 2000;Lionello et al 2006;Gaertner et al 2007;Lionello and Giorgi 2007;Walsh et al 2014;Zappa et al 2015). Indeed, several studies showed the significant contribution of cyclones to the majority of rainfall and wind extremes (e.g., Jansà et al 2001;Nissen et al 2010;Reale and Lionello 2013;RavehRubin and Wernli 2015), to the formation of the most prominent high impact weather events (Llasat et al 2010), as well as to the modulation of the Mediterranean hydrological cycle (Romanski et al 2012;Flaounas et al 2015b).…”
mentioning
confidence: 99%
“…The Mediterranean Sea is one of the most cyclogenetic areas in the world (Campins et al, 2011;Flaounas et al, 2015aFlaounas et al, , 2015b, where explosive cyclogenesis (Lagouvardos et al, 2007) and tropical-like cyclones also occur (Lagouvardos et al, 1999;Tous and Romero, 2013).…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…The Mediterranean cyclones simulated by climate models have been already investigated in some studies as Trigo et al (2002), Lionello et al (2008), Flaounas et al (2013Flaounas et al ( , 2014. In their inter-comparison analysis, Flaounas et al (2016, this issue) already shows that ALADIN is able to simulate correctly some properties (location, intensity) of the Mediterranean cyclones.…”
Section: Simulation Of Mediterranean Cyclones By the Rcm Aladinmentioning
confidence: 98%